Nanoencapsulation of 4-Propylguaiacol in β-Cyclodextrin, Ethyl Cellulose, and Polyvinylpyrrolidone - Margaret W. Kariuki; Ahmed Hassanali; Margaret M. Ng’ang’a (Journal of Chemistry)
We previously identified 4-propylguaiacol to be a highly potent repellent against Rhipicephalus appendiculatus, which transmits East Coast Fever in cattle. So far, the major method that has been employed for tick control is the use of acaricides, which so far has posed a number of challenges. Encapsulation technology may offer a long-term solution to the existing problems by dispensing the repellent at a controlled rate. 4-Propylguaiacol was encapsulated in various nanoparticles, which included β-cyclodextrin, ethyl cellulose, and polyvinylpyrrolidone. The inclusion of 4-propyl guaiacol in the resulting complexes was confirmed by FT-IR, XRD, and SEM analysis. All the sharp peaks belonging to each of the encapsulating polymers were observed. However, some of the characteristic peaks of 4-propylguaiacol disappeared in the complex formed. The rates and duration of release of 4-propylguaiacol from 0.2 g of each inclusion complex were then compared at 38–40°C every 3 hours for 24 hrs. The observed rates of release for 4-propylguaiacol were 0.396 mg/hr., 0.632 mg/hr., and 0.648 mg/hr. Rate from β-cyclodextrin, ethyl cellulose, and PVP inclusion complexes, respectively. The release rate of 4-propylguaiacol in the β-cyclodextrin complex was more controlled than it was in ethyl cellulose and PVP complexes. This controlled release rate exhibited by the β-cyclodextrin complex in small doses for a relatively long time provides a potential tool for dispensing repellents on cattle to protect them from tick bites.